Educação e investimentos externos como determinantes do crescimento a longo prazo - Marone, Guilherme Cortella (1995)
Combining forecast is characterized by an improvement in the accuracy of the prognoses due to the complementarity of the information contained in individual forecasts. This paper follows the seminal work of Bates and Granger (1969) with the objective of investigating whether room exists to improve the accuracy in price index forecasts. There is evidence that even though the gains in combining forecasts are limited, the risks incurred from combining forecasts are less than the benefits gained.